Handling climate change education at universities : an overview - Walter Leal Filho and Mihaela Sima and Ayyoob Sharifi and Johannes M. Lütz and Amanda Lange Salvia and Mark Mifsud and Felicia Motunrayo Olooto and Ilija Djekic and Rosley Anholon and Izabela Rampasso and Felix Kwabena Donkor and Maria Alzira Pimenta Dinis and Maris Klavins and Göran Finnveden and Martin Munashe Chari and Petra Molthan-Hill and Alexandra Mifsud and Salil K. Sen and Erandathie Lokupitiya (Environmental sciences Europe, 2021)
Background: Climate change is a problem which is global in nature, and whose effects go across a wide range of disciplines. It is therefore important that this theme is taken into account as part of universities´ teaching and research programs. Methods: A three-tiered approach was used, consisting of a bibliometric analysis, an online survey and a set of case studies, which allow a profile to be built, as to how a sample of universities from 45 countries handle climate change as part of their teaching programs. Results: This paper reports on a study which aimed at identifying the extent to which matters related to climate change are addressed within the teaching and research practices at universities, with a focus on the training needs of teaching staff. It consists of a bibliometric analysis, combined with an online worldwide survey aimed at ascertaining the degree of involvement from universities in reducing their own carbon footprint, and the ways they offer training provisions on the topic. This is complemented by a set of 12 case studies from universities round the world, illustrating current trends on how universities handle climate change. Apart from reporting on the outcomes of the study, the paper highlights what some universities are doing to handle climate issues, and discusses the implications of the research. Conclusions: The paper lists some items via which universities may better educate and train their students on how to handle the many challenges posed by climate change.
Keywords: Bibliometric analysis; Case studies; Climate change education; Climate change teaching and research; Online worldwide survey; Training needs; Universities